Пошаговое объяснение:
1)
а. 8а + 19а - 28а + 3а = 2а
б. 2,3а +1,8 - 3,2а - 2,4 = -0,9а - 0,6
в. -4х - 11х + 35х - 38х = - 18х
г. 1,6с - 1,2 -3,1с + 0,8 = -1,5с - 0,4
д. 1,1а + 0,9с - 1,2 - 1,3а - 3,8с = -0,2а - 2,9с - 1,2
2)
а. 2 (7а - 6) - 9а = 14а - 12 - 9а = 5а - 12
б. -5х - 4 (8 - 3х) = -5х - 32 - 12х = -17х - 32
в. -3 (2m - 5) - 8 (1 - 6m) = -6m - 15 - 8 - 48m = -54m - 23
г. -7 (3а - 2b) + 2 (5а + 2b) = -21а - 14b + 10а + 4b = -11а - 10b
3)
д. am + bm = m (a + b)
е. 3х - 6у + 9z = общего множителя нет
ж. 5m + 5n - 5 = 5 (m + n)
1) -(14-21х)=56
-14+21х=56
21х=56+14
21х=70
х=70:21
х=3,3
ответ:х=3,3
2)7(х+3)=10х
7х+21=10х
21=10х-7х
21=3х
х=21:3
х=7
ответ:х=7
3)3(х+8)= -3
3х+24= -3
3х= -3-24
3х= -27
х= -27:3
х= -9
ответ:х= -9
4) (45-х)+8=28
45-х+8=28
-х=28-45-8
-х= -25(-1)
х=25
ответ:х=25
5)5х(х-5)= -8х+1
5х(в кв.)-25= -8х+1
(х-5)в кв+8х=1
1.х-5+8х=1 или 2.х-5+8х= -1
9х=1+5
9х=6
х=9:6
х=1,5
2.х-5+8х= -1
9х= -1+5
9х=4
х=9:4
х=2,25
ответ:х1=1,5;х2=2,25
6)3(х-2)=х+2
3х-6=х+2
3х-х=2+6
2х=8
х=8:2
х=4
ответ:х=4
7)(7х+1)-(9х+4)=5
7х+1-9х-4=5
-2х=5-1+4
-2х=8
х=8:(-2)
х= -4
ответ: х= -4
8)5-2(х-1)=4-х
5-2х+2=4-х
-2х+х=4-5-2
-х= -3(-1)
х=3
ответ:х=3.